Transcriptional and post-translational regulation of Flip, an inhibitor of Fas-mediated apoptosis, in human gut inflammation. Issue 12 (14th July 2008) - Caprioli, F; Stolfi, C; Caruso, R; Fina, D; Sica, G; Biancone, L; Pallone, F; Monteleone, G
Abstract : Objective: Defects in Fas-mediated apoptosis are supposed to contribute to the accumulation of T lymphocytes in the gut of patients with Crohn's disease (CD). This phenomenon has been functionally linked with the elevated expression of Flip, an inhibitor of Fas-mediated apoptosis. In this study, the molecular mechanisms that control Flip in CD were examined. Methods: Paired colonic biopsies of patients with CD, patients with ulcerative colitis (UC) and normal controls were analysed for Flip by real-time PCR and western blotting. Flip was also evaluated in CD3 + lamina propria lymphocytes (T-LPLs) cultured with tosyl phenylalanyl chloromethyl ketone (TPCK; a nuclear factor-κB (NF-κB) inhibitor), AG490 (a Janus kinase 2 (Jak2)/signal transducer and activator of transcription (Stat) inhibitor) or 17-desmethoxy-17- N, N -dimethylamino-geldanamycin (DMAG; an inhibitor of heat shock protein 90). The rate of apoptosis was examined by flow cytometry. Results: In CD, upregulation of Flip occurred at both the RNA and protein level. Treatment of CD CD3 + T-LPLs with TPCK or AG490 markedly reduced Flip RNA, suggesting a role for NF-κB and Jak/Stat pathways in the transcriptional control of Flip in this condition. Consistently, both TPCK and AG490 sensitised CD T-LPLs to Fas-mediated apoptosis. Flip protein in cells from normal gut was rapidly degraded by the proteasome pathway. In contrast, in inflamed gut of both CD and UC patients, there was a reduced degradation of Flip via the ubiquitin–proteasome-dependent pathway, but Flip expression can be decreased by DMAG. Conclusions: The data demonstrate that Flip is regulated at both the transcriptional and post-translational level in CD, and indicate that in the normal but not inflamed gut Flip is degraded via the ubiquitin–proteasome-dependent pathway.